Waste Management Policy: Government or Company Responsibility ? - Luckyta Anisti Putri; Chandra Wijaya (Publikasi Indonesia, 2025)
This article aims to analyse the case of water pollution in the Brantas Watershed and explore the application of Corporate Citizenship and Corporate Social Responsibility (CSR) by stakeholders (Companies and Communities located around the Brantas Watershed), and related to industrial and domestic waste management. The main focus of the research is on the social responsibility of the Stakeholders as well as the role of the central government, provincial government, and district/city government in controlling environmental pollution. Using a qualitative approach with a case study method and secondary data analysis, this research describes the various negative impacts of pollution, ranging from damage to the river ecosystem to health risks for the community. The results show that pollution of the Brantas River is caused by the industry's low compliance with waste treatment, weak government supervision, and lack of community participation in protecting the environment. Despite regulatory efforts and legal interventions, policy implementation still faces implementation constraints and limited resources. This research recommends increased supervision, stricter law enforcement, cross-sector collaboration, and community education as strategies to strengthen the sustainability of river management.